Do Community College Presidents and Government Officials Share the Same Perspective? - Barrington, Gail Vallance (Canadian Journal of Higher Education, 1982)
A three-round policy Delphi explored the opinions of Alberta community college presidents and senior officials of Alberta Advanced Education and Manpower regarding the impact of environmental forces as defined by Hall's typology on the development of community colleges in the eighties. Overall, the two groups shared a similar perspective on the environment, as disagreement surfaced on only two major environmental forces. The forces eliciting disagree- ment were Government Priorities Among All Sectors and A Growing Alberta Population.